PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS DI PT KRISTAL KOMPUTERINDO PERKASA - Apriyanti, Eka; Purba, Daris (LPPM Universitas Putera Batam, 2022)
Every humans being are required to know that knowledge of technology and information that continues to grow rapidly. This development follows the times from year to year where this development is maked by a rapid transition because the difference in place and time does not become an obstacle for the community. These studies aims to determine the simultaneous and partial effect of brand image and product quality variabels on purchasing decisions for Asus laptop at PT Kristal Komputerindo Perkasa. The population in the study amounted to 495 with a sample of 222 respondents. Process data used validities test, reliabilities test, classical assumption test, linear regression, t test, F test The results of this study indicate that brand image and product quality influence purchasing decisions. For the brand image variable, the result with a significance and product quality variable with a significance. So that it can be concluded that brand image and product quality have a significant effect on purchasing decisions for Asus laptop at PT Kristal Komputerindo Perkasa.